Safety issues associated with the use and operation of natural gas vehicles: learning from accidents in Pakistan - Khan, M.I.; Yasmin, T.; Khan, N.B. (Springer Verlag, 2016)
The use natural gas in transportation is well established globally with over 18 million natural gas vehicles (NGVs) distributed through more than 90 countries of the world. This paper discusses several safety issues involved with using natural gas as a transportation fuel. After introducing the NGVs safety aspects and reviewing various standards for compressed natural gas (CNG) system, the paper discusses the 55 CNG-related accidents in Pakistan (which conduced to over 250 casualties) and analyzes the causes for these accidents and extracts “lessons to be learned” for CNG. The analysis reveals that due to low-quality CNG system material, e.g., CNG cylinder, CNG design and installation, maintenance system, etc., lack of strict government CNG vehicle safety regulations and driver negligence every year several CNG vehicles’ accidents took place in Pakistan which showed a major threat to life in Pakistan.